Efeitos alelopáticos do exsudato de Microcystis aeruginosa (Kützing) Kützing sobre as respostas fisiológicas de Scenedesmus acuminatus (Lagerheim) Chodat - Miranda, Pâmela Ferreira (2017)
Cyanobacteria have a wide geographical distribution, being important members of the phytoplankton and periphytic communities of marine and freshwater environments. One of the concerns with respect to these organisms lies in their ability to produce secondary metabolites called cyanotoxins, which are highly allelopathic, conferring a competitive advantage on producing species. Many studies suggest that cyanotoxins cause a number of impacts to the entire trophic chain, since they affect the physiology of photoautotrophic organisms. Thus, the present study aims to evaluate the allelopathic effects of the exudate of Microcystis aeruginosa (KÜTZING) KÜTZING on the physiology of Scenedesmus acuminatus (LAGERHEIM) CHODAT. The microalga Scenedesmus acuminatus was submitted to Microcystis aeruginosa producing exudates (MCs+ ) and non-producing (MCs- ) of microcystin at three different concentrations (0.5, 1, 5 µg.L-1 ) and to the control medium (ASM1) totaling six treatments, all in triplicate, which were kept in the culture room at a temperature of 22 ± ºC, 12 h photoperiod of light / dark with a light intensity of approximately (40 µmol.m2.s - 1) and pH at the beginning in the experiment around 7.0 being cultivated for 20 days.Cell density, biovolume, chlorophyll and oxidative stress were analyzed by quantification of the antioxidant enzymes CAT, APX and SOD. The obtained data were submitted to normality tests with posterior analysis of variance ANOVA followed by Tukey test. For non - parametric data the Kruskal - Wallis test was performed with (p <0.05). The results show that the higher concentrations of the toxic treatments (MCs+ 1.0, 5.0) have a significant inhibitory effect on S. acuminatus growth and biovolume. As regards chlorophyll content, the majority of treatments showed a decrease in their values from the 15th day of experimentation. S. acuminatus submitted to concentration of MCs + 5.0 recorded on the 20th day of cultivation the lowest value of chlorophyll a (3.43 µg.mL-1) in relation to the other treatments. However, for the CAT and APX enzymes, there was no significant difference in the antioxidant activity between the treatments in relation to the control on all days of collection; however, the SOD enzyme presented a more evident increase in its activity on days 5, 10 and 15 of treatment in the presence of toxicity (MCs+ 5.0, 1.0, 0.5). Based on the results, it was concluded that the microalgae S. acuminatus showed a heterogeneous response to the stress caused by MCs+ and MCs- exudates, as the high concentrations of MCs+ (1.0, 5.0) were shown to be more sensitive to effects allelopathic from toxic exudates and for some physiological analyzes the MCs- (5.0) treatment was shown to cause equivalent inhibitory effects to the assays exposed to treatments (MCs+ 5.0,1.0).